2019
DOI: 10.1016/j.apenergy.2018.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Open Power System Data – Frictionless data for electricity system modelling

Abstract: The quality of electricity system modelling heavily depends on the input data used. Although a lot of data is publicly available, it is often dispersed, tedious to process and partly contains errors. We argue that a central provision of input data for modelling has the character of a public good: it reduces overall societal costs for quantitative energy research as redundant work is avoided, and it improves transparency and reproducibility in electricity system modelling. This paper describes the Open Power Sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 49 publications
0
48
0
1
Order By: Relevance
“…By the time we first calibrated the model, renewable generation and installed capacity data were provided by netztransparenz.de, which is a data platform initiated by the German TSOs. Meanwhile, all market data used in this analysis are centrally gathered and made publicly available by the Open Power System Data platform (Wiese et al 2019), and can be found here: https ://open-power -syste m-data.org/.…”
Section: Scenarios Data and Calibration Of The Simulationmentioning
confidence: 99%
“…By the time we first calibrated the model, renewable generation and installed capacity data were provided by netztransparenz.de, which is a data platform initiated by the German TSOs. Meanwhile, all market data used in this analysis are centrally gathered and made publicly available by the Open Power System Data platform (Wiese et al 2019), and can be found here: https ://open-power -syste m-data.org/.…”
Section: Scenarios Data and Calibration Of The Simulationmentioning
confidence: 99%
“…For WPP in DK, we used the Open Power System Data platform which provides open data dedicated to electricity system research [28]. The platform is a widely used tool for modeling and scientific research in energy systems in recent years [37–41]. The full data set for DK included 5615 entries for onshore WPP sites in the database.…”
Section: Methods and Datamentioning
confidence: 99%
“…The When2Heat dataset is a contribution to the Open Power System Data project and follows the frictionless data principles 6 . Focusing on the representation of heat pumps, the aim is to improve efficiency, transparency, and reproducibility of electricity market models, which might be part of more general integrated energy system analyses.…”
Section: Background and Summarymentioning
confidence: 99%